Religion, Migration and Social Change: Christian-Muslim Differentials - Foroutan, Yaghoob (Australian religion studies review, 2009)
This paper examines the status of Christian and Muslim Lebanese women in Australia in terms of employment participation. The paper also highlights employment differentials between Lebanese women and non-Lebanese women, both overseas-born and Australian-born, in this multiethnic and multicultural context. Prior studies documented settlement difficulties and a comparatively less economic and socio-demographic circumstances for Lebanese migrants in Australia, especially for women and Muslims. The multivariate outcomes of this paper using the most recent available data nationally representative and focusing on employment status shed further light on the situation and settlement of Lebanese migrant women in Australia since employment status has been observed as a key indication of migrants' settlement and success in the host country.